Relational signalling in governance mechanisms and trust building - Diong, Kah Seng; Foong, Soon Yau; Murali Sambasivan, (Penerbit Universiti Kebangsaan Malaysia, 2018)
‘Thick’ trust is required for the exchange of tacit knowledge in inter-organisational innovation collaborations. Management accounting researchers suggest that when governance mechanisms can provide sufficient mitigations to the relational risks, trusting relationships among the collaborating partners can be developed. However, the question that remains unanswered is why do some collaborative relationships with proper governance structure not lead to the establishment of trust? This study seeks to identify the relational signals in formal governance mechanisms which can foster the development of ‘thick’ trust that is crucial for effective knowledge exchange. Based on the resource-based view (RBV), transaction cost economics theory (TCE), and relational signalling theory, this study proposes a conceptual framework that identifies the relational signalling elements in formal governance mechanisms that can foster ‘thick’ trust among partners. It contributes to the literature by distinguishing specific elements of conventional formal governance mechanisms as relational signalling elements for the effective development of trust among collaborating partners.